Usability evaluation of the agile software process - Wan Ahmad, W.F. (2013)
Agile development methods are most flexible approach for software development where the development team keeps on improving the software with ongoing involvement of user. Despite its flexibility approach in software development, agile methods are still lacking usability evaluation approaches in their development, and integration of usability evaluation into agile development methods is not adequately addressed. In Agile software development, emphasis on requirement gathering and development of comprehensive feasibility reports is not considered in detail. Traditional software development considered this documentation as a quality attribute for the success of the project. Rapid solutions provided by agile software methods leads to the deficiency of good design and architecture which renders the project as expensive. As a remedy, a proposed life cycle for agile software development has been designed. The proposed life cycle outlined in this paper integrates usability evaluation concepts and agile software methodologies for the development of interactive software. To achieve the results, a survey form was formulated and carried out. The results show a greater interest of usability at the initial stage of software development along with user participation and involvement at each stage. The experiment was conducted in the software company by developing an interactive desktop-based application to evaluate the proposed life cycle and IEEE Std. 12207-2008, ISO 9241:210 was used to validate the proposed software model. Â© 2013 Springer International Publishing.